Effect of Foreign Debt on Economic Growth in Indonesia - Cindy Yentika Naibaho; Siti Rahma; Khairani Alawiyah Matondang (PT FORMOSA CENDEKIA GLOBAL, 2023)
Economic development is very important for third world countries, including our country Indonesia, in reducing the distance behind the economy and social welfare from advanced industrial countries. Efforts to develop the economy in these countries which are generally initiated by the government are somewhat limited due to the lack of effective economic resources, the most important of which is capital resources, in particular, which often serve as catalysts for development. In order to meet the shortage of capital resources the government and the countries involved tried to bring in foreign capital through various types of loans. In the short term, foreign debt greatly assists the Indonesian government in its efforts to cover the deficit in the state revenue and expenditure budget. Because routine spending and development spending are quite a lot. So that it can accelerate economic growth faster according to the target. However, in the long term, it turns out that the government's foreign debt can cause various economic problems in Indonesia.